N-formylmethionine-leucyl-phenylalanine protects against irradiation-induced damage to hematopoiesis and intestines - Zhihua Li; Yatong Wu; Jicong Du; Wen Qian; Sinian Wang; Fengsheng Li; Suhe Dong; Shunchang Jiao (BMC, 2024)
Abstract Background Ionizing radiation (IR), including radiotherapy, can exert lasting harm on living organisms. While liposaccharide (LPS) offers resistance to radiation damage, it also induces toxic responses. Thankfully, an LPS analogue called N-formylmethionine-leucyl-phenylalanine (fMLP) holds the potential to mitigate this toxicity, offering hope for radiation protection. Methods Survival of C57BL/6 mice exposed to IR after administration with fMLP/LPS/WR-2721 or saline was recorded. Cell viability and apoptosis assay of bone marrow (BMC), spleen and small intestinal epithelial (HIECs) cells were tested by Cell Counting Kit-8 (CCK-8) and flow cytometry assay. Tissue damage was evaluated by Hematoxilin and Eosin (H&E), Ki-67, and TUNEL staining. RNA sequencing was performed to reveal potential mechanisms of fMLP-mediated radiation protection. Flow cytometry and western blot were performed to verify the radiation protection mechanism of fMLP on the cell cycle. Results The survival rates of C57BL/6 mice exposed to ionizing radiation after administering fMLP increased. fMLP demonstrated low toxicity in vitro and in vivo, maintaining cell viability and mitigating radiation-induced apoptosis. Moreover, it protected against tissue damage in the hematopoietic and intestinal system. RNA sequencing shed light on fMLP's potential mechanism, suggesting its role in modulating innate immunity and cell cycling. This was evidenced by its ability to reverse radiation-induced G2/M phase arrests in HIECs. Conclusion fMLP serves as a promising radioprotective agent, preserving cells and radiosensitive tissues from IR. Through its influence on the cell cycle, particularly reversing radiation-induced arrest in G2/M phases, fMLP offers protection against IR's detrimental effects.